PRICE PERCEPTION, PRODUCT QUALITY, BRAND AMBASSADORS, AND CONSUMER LOYALTY: THE MEDIATION OF CONSUMER SATISFACTION IN SCARLETT COSMETICS: Article - Rahmawati, Christina Heti Tri; Kunda, Henita Susanti; Kristia, Kristia (Jurnal Manajemen, 2022)
Fulfillment of consumer desires and expectations will create satisfaction in consumers so that consumers become loyal. The purpose of this study was to determine 1) the effect of price perceptions on consumer loyalty, 2) the effect of product quality on consumer loyalty, 3) the effect of brand ambassadors on consumer loyalty, 4) the effect of price perceptions on consumer loyalty mediated by consumer satisfaction, 5) the effect of product quality on consumer loyalty by mediating consumer satisfaction, 6) the influence of brand ambassadors on consumer loyalty by mediating consumer satisfaction. The population of this study were all female consumers of Scarlett cosmetics in the Special Region of Yogyakarta. The sample of this research is a portion of Scarlett female consumers in the Special Region of Yogyakarta with criteria aged 16-31 years who have purchased and used Scarlett products at least 2 times for as many as 100 respondents. This study used a sampling technique, namely purposive sampling. Data collection techniques using online questionnaires. This study uses data analysis techniques, namely partial least squares. This study shows the results 1) price perceptions have a significant effect on consumer loyalty 2) product quality has a significant effect on consumer loyalty, 3) brand ambassadors have a significant effect on consumer loyalty, 4) price perceptions have an effect on consumer loyalty partially mediated by customer satisfaction, 5) quality product has no effect on consumer loyalty mediated by consumer satisfaction, and 6) brand ambassadors have an effect on consumer loyalty partially mediated by consumer satisfaction. Keywords: Price Perception; Product Quality; Brand Ambassador; Consumer Loyalty; Consumer Satisfaction